Comparison of Environmental Impacts of Two Alternative Stabilization Techniques on Expansive Soil Slopes - Rui Zhang; Mingxu Long; Jianlong Zheng (Advances in Civil Engineering)
Two alternative techniques, the lime stabilization technique (LST) and the geogrid reinforcement technique (GRT), are both useful to stabilize expansive soil slopes, but their impacts on the environment need be further evaluated. Based on a case study, two techniques as well as their construction processes were introduced. The energy consumption and carbon dioxide (CO2) emissions were investigated by the life cycle assessment (LCA). The sensitivity analyses were carried out, including the lime content for LST, the reinforcement spacing for GRT, the embankment height, delivery distance, and treatment width for both techniques. From the LCA results, with the GRT, the energy consumption and CO2 emissions can be reduced by 7.52% and 57.09%, respectively. The main sources of two techniques are raw material production, soil transportation, and paving stage while the CO2 emissions of lime production are about 11.68 times of those of geogrid production. From the sensitivity analysis results, as the lime content of LST increases by 1%, the total energy consumption and CO2 emissions increase by 8.27% and 13.16%, respectively; as the reinforcement spacing of GRT increases by 0.05 m, the total energy consumption and CO2 emissions increase by 1.63% and 0.69%, respectively; as the embankment height increases by 1 m, the increase rates of energy consumption and CO2 emissions of LST are 1.68 and 1.61 times of those of GRT, respectively. In this project, when the embankment height is less than 10 m, the geogrid technique has the advantages of energy-saving and emission-reduction. It was found that the GRT is not sensitive to the change of delivery distance and treatment width and significantly reduces the environmental impacts, especially in reducing the impact of global warming.